Craniopharyngioma and Metabolic Syndrome: A 5-Year Follow-Up Single-Center Experience - Scarano, Elisabetta; Solari, Domenico; Riccio, Enrico; Arianna, Rossana; Somma, Teresa; Cavallo, Luigi Maria; Romano, Fiammetta; Colao, Annamaria; Di Somma, Carolina (Frontiers in Neurology, 2022)
Patients with craniopharyngioma often have comorbidities, such as obesity and hypopituitarism. These two conditions affect each other and worsen the quality of life of patients, which lead to a higher risk of morbidity and mortality. In addition, abdominal obesity, measured as waist circumference (WC), is together with other parameters [arterial hypertension, hyperglycemia, hypertriglyceridemia, and reduced levels of high-density lipoprotein (HDL) cholesterol], one of the components of metabolic syndrome (MS). Each one of these morbidities occurs in patients with craniopharyngioma more frequently than in the remaining population. On these bases, we evaluated metabolic parameters in patients with craniopharyngioma at the time of diagnosis and after a 5-year follow-up, which compares these data with those of age-, gender-, WC-, and body mass index (BMI)-matched controls. In addition, we evaluated the prevalence of MS according to IDF criteria (MS-IDF) and the prevalence of MS according to ATP III (MS-ATPIII) criteria in patients and controls at baseline and after 5 years. We recruited 20 patients with craniopharyngioma (age 38.5 ± 15 years, 10 M) and 20 age-, gender-, WC- and BMI-matched controls (age 34.16 ± 13.19 years, 10 M). In all patients and controls, we evaluated the following: anthropometric features [height, weight, BMI, WC, hip circumference (HC) and waist-to-hip ratio (WHR)], systolic blood pressure (SBP) and diastolic blood pressure (DBP), lipid profile [total cholesterol (TC), HDL, low-density lipoprotein (LDL) cholesterol, triglycerides (TG)], and blood glucose at baseline and after 5 years. The prevalence of MS, according to IDF and ATPIII criteria, was calculated in the two groups at baseline and after 5 years. According to our results, at baseline, patients with craniopharyngioma had a worse metabolic profile than controls and a higher prevalence of MS. Besides, at a 5-year follow-up, patients still had impaired metabolic characteristics and more frequent MS (according to IDF and ATPIII criteria) when compared to controls. These data confirm that MS in patients with craniopharyngioma is unresponsive to life-changing interventions and to a common pharmacological approach. Other factors may be involved in the evolution of these conditions; so, further studies are needed to establish the correct management of these patients.